Contextualizing English Speaking Instruction in Indonesian Pesantren:: A Needs Analysis - Attabik, Muhammad Haikal; Sugesti, Nunik; Zainiza, Mailiza; Khusuma Dewi, Anggraeni; Ahdiansyah, Agung (International Journal of Language Teaching and Education, 2026)
This study investigates the target needs, learning needs, and environmental factors influencing English-speaking instruction in an Indonesian pesantren context. Employing a mixed-methods design, data were collected through questionnaires administered to 20 santri (10 male and 10 female) and semi-structured interviews with two English teachers at Pesantren Babakan Ciwaringin Cirebon. The findings reveal that English is primarily used in routine communicative situations, particularly daily conversations and speech-related activities. Daily activity stopics and contextual expressions are perceived as the most relevant speaking content, while grammar emerges as both the greatest speaking difficulty and the most desired aspect to master. Although santri demonstrate adequate performance in basic communication, they experience difficulties in higher-order speaking activities, such as debate, argumentation, and spontaneous discussion. The study also highlights the important role of environmental support, including teacher guidance, peer interaction, institutional language policies, and extracurricular activities, in promoting English use. However, regular language exposure does not necessarily lead to communicative competence, as speaking practices remain largely routine-oriented and accuracy-focused. The study suggests that speaking instruction in pesantren should incorporate more contextualized and interaction-focused activities to support the development of higher-order communicative competence.